Mammadov, Mahabbat - (:unkn) unknown (My University, 2026)
Mahabbat Ashir Mammadov graduated from the Azerbaijan State Oil and Chemistry Institute in 1974 with a degree in Economics and Engineering. From 1974 to 1980, he worked as an economist and senior economist at the Republican Computing Center of the State Committee for Material and Technical Supply of the Republic of Azerbaijan. From 1980 to 1993, he served as Deputy Head of the Department of Higher Education and Science at the Ministry of Higher and Secondary Specialized Education, while also teaching at the Azerbaijan Institute of Civil Engineers. In 2009, he defended his doctoral dissertation on program-target management in a transition economy and was awarded the degree of Doctor of Economic Sciences. In 2012, he was awarded the academic title of Professor in Economics and Management of the National Economy. Professor Mammadov has received several national awards for his contributions to education, science, and the development of Azerbaijan's industrial and energy sectors, including the Progress Medal awarded by the President of the Republic of Azerbaijan in 2016. Since 2015, he has served as Editor-in-Chief of the Construction Economics and Management journal. He is also a member of several national and international academic editorial boards and professional organizations. In 2026, he became a reviewer for Polityka Energetyczna (Energy Policy Journal) and was elected a Full Member (Academician) of the Asian Academy of Sciences.